2010
DOI: 10.1515/cclm.2010.228
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of MTHFR C677T variant to the risk of diabetic nephropathy in Lebanese and Bahraini Arabs

Abstract: The contribution of C677T single nucleotide polymorphism to increased risk of DN (presumably by increasing homocysteine concentrations) must be evaluated in the context of the ethnic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…Sun et al [38 ]reported that among the Chinese population with T2DM, MTHFR C677T polymorphism may be a genetic risk factor for diabetic nephropathy. However, some studies did not demonstrate any association between diabetic nephropathy and MTHFR A1298C polymorphism [36,39]. Furthermore, it was demonstrated in Lebanese T2DM patients that the 677T allele but not the 1298C allele was a risk factor for diabetic nephropathy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [38 ]reported that among the Chinese population with T2DM, MTHFR C677T polymorphism may be a genetic risk factor for diabetic nephropathy. However, some studies did not demonstrate any association between diabetic nephropathy and MTHFR A1298C polymorphism [36,39]. Furthermore, it was demonstrated in Lebanese T2DM patients that the 677T allele but not the 1298C allele was a risk factor for diabetic nephropathy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies 4,[15][16][17][18][19][20][21] reporting the relationship between MTHFR A1298C gene polymorphism and T2DN susceptibility were recruited into this meta-analysis. The data of our interest were extracted (Table 1) and the included investigations contained 1387 patients with T2DN and 1533 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The role of SNPs in diabetic nephropathy has been previously analyzed in Arab countries (Ezzidi et al, 2009;Nemr et al, 2010). However, we are the first to report the association between these SNPs and diabetic nephropathy in the Middle-Eastern Arab region.…”
Section: Discussionmentioning
confidence: 90%